PROFIL REPRESENTASI VISUAL MAHASISWA PADA MATA KULIAH GEOMETRI - Najmah Istikaanah; Muhammad Prayito (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
The specific purpose of this study is to determine the profile of visual representation of students in geometry courses. This research is a qualitative research. The data collection method is done through documentation, observation, learning achievement tests and questionnaires. The results showed that the ability of visual representation of 1st semester students at mathematics education was still low. This is reviewed in the student's ability to answer learning achievement test at geometry courses.